A New Modular Multilevel Converter Topology for Green Hydrogen Production - Espina-Gonzalez, E; Diaz-Diaz, M; Pizarro-Jimenez, P; Ravet-Orellana, T (Institute of Electrical and Electronics Engineers Inc., 2023)
The production of hydrogen through electrolysis is an already known process, and many power converters have been proposed as interfaces between the energy sources and the electrolyzers. On the other hand, in the last few years, modular multilevel cascaded converters have been proposed in many applications, such as high-power AC to AC or DC to AC conversion. Still, little to no references present this family of converters for hydrogen production, mainly because electrolysis requires the operation of a high-current, low-voltage port, limiting the options for this family of power converters. Therefore, this paper proposes a new topology for the modular multilevel cascaded converter and a control strategy to feed a proton exchange membrane electrolyzer using solar photovoltaic energy and the grid; this topology is theπ-MMC 1ϕ Several simulation results are carried out to validate the proposed topology and the control strategy. © 2023 IEEE.
Keywords: Green hydrogen; MMCC; Pi modular multilevel converter; Solar energy